Thermodynamic analysis of dry autothermal reforming of glycerol - Kale, Ganesh R.; Kulkarni, Bhaskar D. (Fuel Processing Technology, 2010)
{Dry autothermal reforming of glycerol uses a combination of dry (CO(2)) reforming and partial oxidation reactions to produce syngas rich product stream. Thermodynamic equilibrium data for dry autothermal reforming of glycerol was generated for temperature range 600-1000 K . 1 bar pressure, OCGR [feed O(2)/C (C of glycerol only) ratio] 0.1 to 0.5 and CGR [feed CO(2)/glycerol ratio] 1 to 5 and analyzed. The objective of the paper is to identify the thermodynamic domain of the process operation, study the variation of product distribution pattern and describe the optimum conditions to maximize yield of the desired product and minimize the undesired product formation. Higher OCGR and higher CGR yielded a syngas ratio (similar to 1), with lower carbon and methane formation, while lower CGR and lower OCGR yielded good hydrogen and total hydrogen, with low water and CO2 production. The best thermoneutral condition for DATR of glycerol operation was seen at a temperature of 926.31 K at 1 bar pressure
Keywords: CO(2) reforming; Dry reforming; Glycerol reforming; Syngas production; Thermodynamic modeling

Thermodynamic study of combining chemical looping combustion and combined reforming of propane - Kale, Ganesh R.; Kulkarni, Bhaskar D.; Joshi, Ajit R. (Fuel, 2010)
Existing energy generation technologies emit CO(2) gas and are posing a serious problem of global warming and climate change. The thermodynamic feasibility of a new process scheme combining chemical looping combustion (CLC) and combined reforming (CR) of propane (LPG) is studied in this paper. The study of CLC of propane with CaSO(4) as oxygen carrier shows thermodynamic feasibility in temperature range (400-782.95 degrees C) at 1 bar pressure. The CO(2) generated in the CLC can be used for combined reforming of propane in an autothermal way within the temperature range (400-1000 degrees C) at 1 bar pressure to generate syngas of ratio 3.0 (above 600 degrees C) which is extremely desirable for petrochemical manufacture. The process scheme generates (a) huge thermal energy in CLC that can be used for various processes, (b) pure N(2) and syngas rich streams can be used for petrochemical manufacture and (c) takes care of the expensive CO(2) separation from flue gas stream and CO(2) sequestration. The thermoneutral temperature (TNP) of 702.12 degrees C yielding maximum syngas of 5.98 mol per mole propane fed, of syngas ratio 1.73 with negligible methane and carbon formation was identified as the best condition for the CR reactor operation. The process can be used for different fuels and oxygen carriers. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Chemical looping combustion; CLC; CO(2) utilization; Energy generation

Thermoneutral point analysis of ethanol dry autothermal reforming - Kale, Ganesh R.; Kulkarni, Bhaskar D. (Chemical Engineering Journal, 2010)
{Dry autothermal reforming of ethanol can be used to produce a variety of value added products like hydrogen, syngas and also carbon (possible CNF). A thermodynamic analysis of dry autothermal reforming of ethanol has been carried out to locate the thermoneutral temperatures and product composition at those points at 1, 3, 6 and 9 bar reaction pressures. The variations of thermoneutral temperatures and individual product yields at those temperatures have been discussed to find the optimum operating parameters for desired product output from the process. The process operated at thermoneutral conditions can give useful products like hydrogen, syngas (of low ratio) and carbon (possibly CNFs) and also provide a way for CO2 sequestration using renewable ethanol fuel. A maximum of 2.58 moles of syngas of ratio 2.01 obtained at 1 bar
Keywords: CO2 utilization; Dry autothermal reforming; Ethanol reforming; Thermoneutral

Alternative process for gasoline fuel processors - Kale, Ganesh R.; Kulkarni, Bhaskar D. (International Journal of Hydrogen Energy, 2011)
The article explores the thermodynamics of an alternate hydrogen generation process dry autothermal reforming and its comparison to autothermal reforming process of isooctane for use in gasoline fuel processors for SOFC. A thermodynamic analysis of isooctane as feed hydrocarbon for autothermal reforming and dry autothermal reforming processes for feed OCIR (oxygen to carbon in isooctane ratio) from 0.5 to 0.7 at 1 bar pressure under analogous thermoneutral operating conditions was done using Gibbs free energy minimization algorithm in HSC Chemistry. The trends in thermoneutral points (TNP), important product gas compositions at TNPs and fuel processor energy requirements were compared and analyzed. Dry autothermal reforming was identified as a less energy consuming alternative to autothermal reforming as the syngas can be produced with lower energy requirements at thermoneutral temperatures, making it a promising candidate for use in gasoline fuel processors to power the solid oxide fuel cells. The dry autothermal reforming process for syngas production can also be used for different fuels. (C) 2010 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.
Keywords: Autothermal reforming; Dry autothermal reforming; hydrogen production; Isooctane reforming; Thermodynamic modeling

Chemical looping reforming of ethanol for syngas generation: a theoretical investigation - Kale, Ganesh R.; Kulkarni, Bhaskar D.; Bharadwaj, K. V. (International Journal of Energy Research, 2013)
Chemical looping reforming (CLR) is a novel technology that can be used for reforming of cheaply available abundant biofuel like ethanol for the production of hydrogen/syngas for fuel cells. A systematic thermodynamic study for the CLR process using selected oxygen carriers was done to analyze the products and energy requirements of the CLR process in the temperature range of 5001200 degrees C at 1bar pressure for ethanol. The results showed favorable conditions for syngas manufacture from this process. Fe2O3 was found to be the best performing oxygen carrier followed by calcium and sodium sulfates, while Mn oxides were the least preferred oxygen carriers for CLR of ethanol process. The optimum process temperature was found to be 1000 degrees C. The actual CLR-ethanol process shows exothermicity against the theoretical endothermic partial oxidation of ethanol. The results obtained in this theoretical study can pave the way for experimental programs for syngas generation for SOFC-type fuel cells. Similar studies can be undertaken for other fuels for fuel processor development by CLR process. Copyright (c) 2012 John Wiley & Sons, Ltd.
Keywords: chemical looping reforming; ethanol to syngas; Fuel Processor; Gibbs minimization; oxygen carriers

Hydrogen generation with CO2 utilization: a solvay cluster study - Kale, Ganesh R.; Kulkarni, Bhaskar D. (International Journal of Hydrogen Energy, 2013)
The fuel cell economy is yet to start research programs in hydrogen generation with CO2 utilization for hydrocarbon reforming processes used in fuel processor applications. A simple thermodynamic study using solvay clusters was done to investigate the feasibility of using the carbon species produced in the steam methane reforming process to produce value added chemicals. The results of this study are highly encouraging to start process development of closed systems of hydrogen generation with CO2 conversion to acetic acid/acrylic acid making easier the commercialization of fuel cells and hydrogen energy. Such studies can be specifically carried out for different fuel processor systems. Copyright (C) 2012, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: CO2 utilization; Fuel processing; Gibbs energy; Solvay clusters; Steam reforming

Combined gasification of lignite coal: thermodynamic and application study - Kale, Ganesh R.; Kulkarni, Bhaskar D.; Chavan, Rank N. (Journal of the Taiwan Institute of Chemical Engineers, 2014)
Combined gasification (a combination of steam gasification and CO2 gasification) without air is an important process for research in coal gasification to reduce the steam generation energy in the gasification system and also to enhance the slow CO2 gasification reaction. A thermodynamic study involving the effect of temperature, pressure and feed CO2 and steam ratios in gasification of lignite coal was studied in this paper. The product generation trends of syngas and methane with carbon (in coal) conversion were studied in detail. The carbon (in lignite coal) was converted completely at a lower temperature than pure carbon in the combined gasification. Some applications of the gasifier product gas were also studied. Combined gasification offers great advantages to produce syngas of exact ratio in one step for use in petrochemical manufacture and fuel cell systems. The complete carbon (in coal) conversion occurred beyond the thermoneutral gasification temperature in the study. The combined gasification process was a useful way for CO2 utilization reducing the net CO2 emission to the atmosphere. (C) 2013 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: CO2 utilization; Coal gasification; Coal to syngas; Combined gasification; Thermodynamic study

Thermoneutral conditions in dry reforming of ethanol - Kale, Ganesh R.; Kulkarni, Bhaskar D. (Asia-Pacific Journal of Chemical Engineering, 2014)
The reaction enthalpy (Delta H) of reforming processes like steam and dry (CO2) reforming is of great importance for scale-up and process development. Generally, the reforming processes are considered endothermic in nature. However, a detailed study of the reaction enthalpy of reforming process, taking the example of dry reforming of ethanol considered in this study, reveals the existence of exothermic reaction enthalpy at low temperatures. A study of reaction enthalpy of ethanol dry reforming within pressure (1-10 bar), temperature range (300-900 degrees C), and CO2 to carbon in ethanol ratio (CCER 1-5) was initiated to determine the existence of thermoneutral temperatures for the overall reaction. The variation of thermoneutral conditions and product yields at the thermoneutral temperatures was studied. The utilization potential of the products generated at thermoneutral conditions was also evaluated. The low-pressure thermoneutral operation favored higher hydrogen production, lower methane and water formation, whereas the high-pressure thermoneutral operation favored product gas of lower syngas ratio with higher CO2 conversion (utilization) in the process. The study can be extended to steam and dry reforming of other fuels to generate valuable products at thermoneutral conditions avoiding use of air in the process and subsequent N-2 dilution of the product gas. (c) 2013 Curtin University of Technology and John Wiley & Sons, Ltd.
Keywords: carbon nanofilaments; CO2 utilization; Dry reforming; ethanol to syngas; thermoneutral process

Nanostructure oxygen carrier used in chemical looping combustion process-A review - Badadare, Mansing M.; Adbale, Naina M.; Khomane, Ramdas B.; Kale, Ganesh R. (Advanced Science Letters, 2016)
Chemical looping combustion (CLC) is an emerging technology with inherent separation of CO2 from combustion of fuels. In this technique contact of air and fuel for combustion is restricted by providing oxygen through oxygen carrier (DC). The functional efficiency of CLC process mainly depends on the ability of oxygen carrier and it's reactivity, which undergoes repeated oxidation and reduction cycles. Nanostructure metal oxides have shown great potential application in the field of chemical looping combustion due to their high surface to volume ratio and enhanced structural properties. Synthesis technique of nanostructure metal oxides, their role as oxygen carrier, their reactivity with fuels along with their structural stability are reviewed herein. The contribution of various operating conditions on nanostructure oxygen carrier are considered in this review. These operating conditions and synthesis routes are summarized and classified according to metal oxides.
3rd International Conference on Nanotechnology, Pune, INDIA, OCT 14-15, 2014
Keywords: Chemical looping combustion; CO2 Emission; Metal Oxide; Nanostructure; Oxygen Carrier